Post-consumer recovery of high content polycarbonates
By using a high-level post-consumption recovery of polycarbonate and specific additives in the polycarbonate molded structure, the problem of insufficient flame retardant performance of polycarbonate molded structures in the prior art is solved, and excellent flame retardant is achieved Performance and physical performance, meet UL V-0 rating.
Patent Information
- Application Number
- CN202380048227.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-12
- Filing Date
- 2023-07-12
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art is difficult to improve the flame retardant properties of the polycarbonate molded structure while maintaining excellent properties of the polycarbonate molded structure, especially when meeting the requirements of the UL V-0 rating.
Compositions are employed that include high levels of post-consumer recovery polycarbonate, original polycarbonate, silicon compounds with branched structures and organic functional groups, anti-drop agents, organometallic salts, carbon-based particles or metal oxides, and buffer compounds. The composition improves the flame retardant and mechanical properties of the composition through specific combinations and additives.
It achieves a high level of post-consumption recycling content, and has excellent flame retardant properties and physical properties, meets the UL94 V0@1.4mm rating, and maintains ductility at high temperatures.
Smart Images

Figure BDA0005197100760000051 
Figure BDA0005197100760000061 
Figure BDA0005197100760000101
Abstract
Description
Technical Field
[0001] Disclosed are polycarbonate compositions containing high levels of post-consumer recycled content, wherein the compositions exhibit high levels of flame retardancy and excellent physical properties. Disclosed are methods of making such compositions. Disclosed are structures made from the disclosed compositions. Background Art
[0002] Polycarbonate and copolymers containing carbonate units are used in various molded structures. Polycarbonate and copolymers containing carbonate units form rigid molded structures. Molded structures can be used for a variety of purposes, including housings for electronic devices, automotive parts, medical devices, household appliances, speakers, household items, etc. The flame retardancy of such structures is an important safety consideration. The market continues to require improved flame retardancy while maintaining the excellent performance of molded structures. It is necessary to recycle used polycarbonate or its copolymers. It is desirable to use recycled polycarbonate or its copolymers in molded products as long as the structure provides flame retardancy and maintains excellent performance. Recycled polycarbonate and its copolymers can be derived from post-consumer waste, such as water bottles, soda bottles, etc. Such recycled polycarbonate may contain polyester impurities, for example, in an amount of 0.1-1.0 weight %. The presence of polyester may have a negative impact on the flame retardancy of the structure containing recycled polycarbonate. Significant progress has been made in developing polycarbonate formulations containing post-consumer recycled polycarbonate, see WO2019 / 115506, which discloses a laminate containing a fiber base layer and a polycarbonate-based layer, wherein up to fifty percent of the polycarbonate may be post-consumer recycled polycarbonate. Many polycarbonate users want to use polycarbonate with a higher post-consumer recycled content and require flame retardancy that achieves a UL V-0 rating while also having the excellent physical properties of virgin polycarbonate.
[0003] What is needed are compositions containing high levels of post-consumer recycled polycarbonate that form molded structures having desirable flame retardancy while maintaining the superior properties of molded products containing polycarbonate, such as excellent tensile strength at yield, tensile strength at break, tensile elongation at yield, tensile elongation at break, notched Izod impact strength, etc. What is also needed are molding compositions prepared from such compositions that exhibit improved flame retardancy and such superior properties. Summary of the invention
[0004] A composition is disclosed, comprising: a) about 30 weight percent or more of one or more post-consumer recycled polycarbonates, b) about 5 weight percent or more of one or more virgin polycarbonates, c) one or more silicon compounds having a branched structure and an organic functional group, d) one or more anti-drip agents, e) one or more organic metal salts, f) one or more carbon-based particles, metals or metal oxides, and g) one or more buffer compounds, such as alkali metal phosphates, wherein the weight percentages are based on the total weight of the composition. A composition comprising 50 weight percent or more of one or more post-consumer recycled polycarbonates, about 75 weight percent or more of one or more post-consumer recycled polycarbonates, or about 90 weight percent or more of one or more post-consumer recycled polycarbonates is disclosed. The disclosed composition may include c) about 0.1 to about 3 weight % of one or more silicon compounds having a branched structure and an organic functional group, d) about 0.01 to about 2 weight % of one or more anti-drip agents, e) about 0.01 to about 2 weight % of one or more organic metal salts, f) about 0.02 to about 10 weight % of one or more carbon-based particles, metals or metal oxides, and g) about 0.02 to about 0.2 weight % of one or more alkali metal phosphates, wherein the weight percentages are based on the total weight of the composition. The disclosed composition may include c) about 0.1 to about 1.5 weight % of one or more silicon compounds having a branched structure and an organic functional group, d) about 0.01 to about 2 weight % of one or more anti-drip agents, e) about 0.01 to about 1.0 weight % of one or more organic metal salts, f) about 0.03 to about 5 weight % of one or more carbon-based particles, metals or metal oxides, and g) about 0.02 to about 0.1 weight % of one or more buffer compounds, such as alkali metal phosphates, wherein the weight percentages are based on the total weight of the composition. The one or more organometallic salts may include one or more perfluoroalkyl sulfur compounds or aromatic sulfur compounds, which may be present in an amount of about 0.05 to about 0.4 weight percent based on the total weight of the composition.
[0005] The composition may include one or more non-halogenated flame retardants. The composition may include one or more antioxidants. The composition may include one or more UV absorbers or one or more impact modifiers. The composition may include one or more release agents. The composition may include one or more colorants.
[0006] One or more metal oxides may include one or more of titanium dioxide, magnesium oxide and silicon dioxide. One or more carbon-based particles may be carbon black or carbon nanotubes. The buffer compound may include one or more alkali metal phosphates, such as one or more distearyl pentaerythritol diphosphates, monohydrogen phosphates or dihydrogen phosphates and monohydrogen phosphate, dihydrogen phosphate or trihydrogen phosphate compounds. One or more alkali metal phosphates may include one or more monohydrogen phosphate, dihydrogen phosphate or trihydrogen phosphate compounds. One or more alkali metal phosphates may include sodium dihydrogen phosphate or disodium phosphate. According to ASTM D1238, the melt flow rate of polycarbonate recycled after consumption and / or original polycarbonate may be from about 1 to about 30 grams / 10 minutes.
[0007] Disclosed are articles made from the compositions disclosed herein.
[0008] A method is disclosed, comprising: a) contacting and mixing the ingredients of any of the compositions disclosed herein at a temperature of about 250° C. or higher for about 4 minutes or longer, b) filling a mold with the mixed composition of a), and c) forming the composition in the mold into a solid article, and d) removing the formed article from the mold. The contact mixing can be performed in an extruder and the formed mixture can be moved from the extruder to the mold.
[0009] Compositions and structures prepared from such disclosed compositions show high post-consumer recycled content. Articles prepared from the composition achieve UL94 V0@1.4mm flame retardancy. Articles prepared from the composition maintain ductility when processed at about 300°C and a residence time of 7 minutes or more. Articles prepared from the composition exhibit notched Izod impact strength of about 680 J / m or more or 700 J / m or more, with a standard deviation of about 25 J / m or less. The articles can be used in automobiles, trains, buses, recreational vehicles (RVs), etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 The dimensions of the injection molding machine screw and barrel used and the formula used to calculate the residence time are shown. DETAILED DESCRIPTION
[0011] While the present disclosure has been described in conjunction with certain embodiments, it should be understood that the present disclosure is not limited to the disclosed embodiments, and is intended to cover various modifications and equivalent arrangements included within the purview of the appended claims, the scope of which is to be given the broadest interpretation so as to encompass all such modifications and equivalent structures permitted by law.
[0012] As used herein, one or more means that at least one or more than one of the listed components can be used as disclosed. As used herein, a hydrocarbyl group refers to a group containing one or more carbon atom backbones and hydrogen atoms, which group may optionally contain one or more heteroatoms. When a hydrocarbyl group contains heteroatoms, the heteroatoms may form one or more functional groups known to those skilled in the art. The hydrocarbyl group may contain any combination of alicyclic, aliphatic, aromatic or such segments. The aliphatic segment may be straight chain or branched. The aliphatic and alicyclic segments may contain one or more double bonds and / or triple bonds. The hydrocarbyl group includes alkyl, alkenyl, alkynyl, aryl, cycloalkyl, cycloalkenyl, alkaryl and aralkyl groups. The alicyclic group may contain both cyclic and non-cyclic parts. Hydrocarbylene means a hydrocarbyl group or any described subset having more than one valence state, such as alkylene, alkenylene, alkynylene, arylene, cycloalkylene, cycloalkenylene, alkarylene and aralkylene. As used herein, valence refers to a covalent bond between a hydrocarbyl or hydrocarbylene group and another group such as a carbonyl, oxygen, nitrogen or sulfur containing group or atom or the base compound mentioned. Unless otherwise stated, weight % or weight parts as used herein refer to or are based on the weight of the composition. Tg is the temperature or temperature range at which a sudden change occurs in the physical properties of a polymeric material, including, for example, mechanical strength. Tg can be determined by differential scanning calorimetry (DSC). As used herein, "post-industrial" refers to a source of material generated during the manufacture of goods or products. As used herein, "post-consumer" refers to a source of material generated after the final consumer uses the consumer goods or products made from the material.
[0013] A composition comprising one or more polycarbonates is disclosed, wherein one or more polycarbonates recycled after consumption are contained, accounting for 95% of the weight of the composition. The disclosed composition may contain virgin polycarbonate. Virgin polycarbonate is a polycarbonate that has not been used in any composition before. Such a composition may contain one or more of the following: one or more silicon compounds with a branched structure and an organic functional group, one or more anti-drip agents, one or more organic metal salts, one or more carbon-based particles, metals or metal oxides, and one or more buffer compounds (e.g., alkali metal phosphates). The composition may contain one or more non-halogenated flame retardants, one or more antioxidants, one or more UV absorbers, one or more impact modifiers, one or more release agents and / or one or more colorants. As disclosed herein, the presence of one or more carbon-based particles, metals or metal oxides and / or one or more buffer compounds (e.g., alkali metal phosphates) is conducive to the disclosed composition containing a high level of polycarbonate recycled after consumption, while showing good flame retardancy and excellent excellent performance.
[0014] As used herein, polycarbonate means a polymer containing carbonate units. Such polymers can be homopolymers consisting essentially of carbonate monomer units or copolymers containing one or more other monomer units (comonomer units) and carbonate units. Such copolymers can be block copolymers containing blocks of two or more different monomer units, or can be random copolymers in which different monomer units are randomly distributed on the polymer backbone. If the intended use requires, additional monomer units may include any monomer units that do not have a negative impact on the inherent properties of polycarbonate (such as heat resistance, impact resistance, moldability, flexural modulus, flexural strength, flexural strength, haze and transparency). Exemplary comonomer units include ester units, polysiloxane units, etc. As disclosed herein, the amount of carbonate monomer units in the copolycarbonate is selected so that the resulting polymer retains the desired properties of polycarbonate. Copolycarbonate can include carbonate monomer units greater than 50 mole % of carbonate monomer units, about 75 mole % or more of carbonate monomer units, about 80 mole % or more of carbonate monomer units, or about 85 mole % or more of carbonate monomer units. Copolycarbonate can comprise about 99 mol % or carbonate monomer units still less, about 97 mol % or carbonate monomer units still less or about 95 mol % or carbonate monomer units still less.Copolycarbonate can comprise about 1 mol % or more comonomer units, about 3 mol % or more comonomer units or about 5 mol % or more comonomer units.Copolycarbonate can comprise comonomer units, about 25 mol % or less comonomer units, about 20 mol % or less comonomer units or about 15 mol % or less comonomer units that are less than 50 mol %.Polycarbonate units can comprise aromatic units in the main chain of polymer.
[0015] The production of polycarbonates is achieved, for example, by reacting diphenols with carbonic acid halides (preferably phosgene) and / or with aromatic dicarboxylic acid dihalides (preferably benzenedicarboxylic acid dihalides) by the phase boundary process, optionally using chain terminators (e.g. monophenols) and optionally using trifunctional branching agents or branching agents with a functionality greater than 3 (e.g. trisphenols or tetraphenols). The diphenols used to produce aromatic polycarbonates and / or aromatic polyester carbonates may correspond to the formula I
[0016]
[0017] Where A represents a single bond, C 1-5 Alkylene, C 2-5 Alkylene, C 5-6 Cycloalkyl, -O-, -SO-, -CO-, -S-, -SO 2- or C 6-12 Arylene to which further aromatic rings may be fused, said aromatic rings optionally containing heteroatoms, or groups of the formula II or III:
[0018]
[0019] wherein B is independently at each occurrence hydrogen, C 1-12 Alkyl, preferably methyl or halogen, preferably chlorine and / or bromine;
[0020] x is in each case independently 0, 1 or 2;
[0021] p is 0 or 1;
[0022] R c and R d Independent of each other, can be targeted for each X 1 Selected individually and is hydrogen or C 1-6 Alkyl, preferably hydrogen, methyl or ethyl;
[0023] X 1 represents carbon; and
[0024] m represents an integer from 4 to 7, preferably 4 or 5, provided that R c and R d At least one X 1 The alkyl group on the atom.
[0025] Exemplary diphenols are hydroquinone, resorcinol, dihydroxybiphenyl, bis(hydroxyphenyl)-C 1-5 Alkanes, bis(hydroxyphenyl)-C 5-6 Cycloalkanes, bis(hydroxy-phenyl) ethers, bis(hydroxyphenyl) sulfoxides, bis(hydroxyphenyl) ketones, bis(hydroxy-phenyl) sulfones and 4,4″-bis(hydroxyphenyl) diisopropylbenzene, and derivatives thereof having a brominated and / or chlorinated nucleus. Particularly preferred diphenols are 4,4′-dihydroxybiphenyl, bisphenol A, 2,4-bis(4-hydroxyphenyl)-2-methyl-butane, 1,1-bis(4-hydroxyphenyl)-cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethyl-cyclohexane, 4,4-dihydroxydiphenyl sulfide and 4,4-dihydroxydiphenyl sulfone, and dibrominated and tetrabrominated or chlorinated derivatives thereof, such as 2,2-bis(3-chloro-4-hydroxyphenyl)- 2,2-bis-(4-hydroxyphenyl)propane (bisphenol A) is particularly preferred. The diphenols can be used alone or in any mixture. The diphenols are known from the literature or can be obtained by methods known from the literature. In addition to bisphenol A homopolycarbonates, exemplary polycarbonates include copolycarbonates of bisphenol A having up to 15 mol % of other disclosed diphenols, such as 2,2-bis(3,5-dibromo-4-hydroxyphenyl)-propane, relative to the molar sum of the diphenols.
[0026] Exemplary chain terminators for producing polycarbonate include phenolic compounds, including phenol, p-chlorophenol, p-tert-butylphenol, 4-(1,3-dimethyl-butyl)-phenol, and 2,4,6-tribromophenol; long-chain alkylphenols, such as monoalkylphenols or dialkylphenols containing a total of 8 to 20 carbon atoms in their alkyl substituents, exemplified by 3,5-di-tert-butylphenol, p-isooctylphenol, p-tert-octylphenol, p-dodecylphenol, 2-(3,5-dimethylheptyl)-phenol, and 4-(3,5-dimethylheptyl)-phenol. The amount of chain terminator used may be about 0.1 mol% or more, based on the molar sum of the diphenols used in each case. The amount of chain terminator used may be about 10 mol% or less, based on the molar sum of the diphenols used in each case.
[0027] The polycarbonate can be branched, for example, by incorporating from about 0.05 to about 2.0 mole % of a trifunctional compound or a compound having a functionality higher than 3, such as those containing four or more phenolic groups, relative to the total amount of diphenols used. Branched polycarbonates used in the disclosed compositions can be prepared by known techniques, for example, several methods are disclosed in USP 3,028,365, 4,529,791 and 4,677,162 (which patents are hereby incorporated by reference in their entirety). Exemplary branching agents include tri- or polyfunctional carboxylic acid chlorides such as trimesic acid trichloride, cyanuric acid trichloride, 3,3'-,4,4'-benzophenonetetracarboxylic acid tetrachloride, 1,4,5,8-naphthalene-tetracarboxylic acid tetrachloride or pyromellitic acid tetrachloride in an amount of about 0.01 to about 1.0 mole % (relative to the dicarboxylic acid dichloride used), or tri- or polyfunctional phenols such as phloroglucinol, 4,6-dimethyl-2,4,6-tris(4-hydroxyphenyl)-2-heptene, 4,4-dimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)-benzene, 1 , 1,1-tris(4-hydroxyphenyl)ethane, tris(4-hydroxyphenyl)-phenyl-methane, 2,2-bis[4,4-bis(4-hydroxyphenyl)cyclohexyl]-propane, 2,4-bis[1-(4-hydroxyphenyl)-1-methyl-ethyl]phenol, tetrakis(4-hydroxyphenyl)-methane, 2,6-bis(2-hydroxy-5-methyl-benzyl)-4-methyl-phenol, 2-(4-hydroxyphenyl)-2-(2,4-dihydroxyphenyl)propane or tetrakis(4-[1-(4-hydroxyphenyl)-1-methylethyl]-phenoxy)-methane, which is about 0.01 to about 1.0 mol% relative to the amount of diphenol used. A phenolic branching agent can be placed in the reaction vessel together with the diphenol. An acyl chloride branching agent can be introduced together with the acyl chloride.
[0028] Copolycarbonates can be prepared by known methods. For example, polydiorganosiloxanes containing hydroxyaryloxy end groups of about 1 to about 25 parts by weight, about 2.5 to about 25 parts by weight (relative to the total amount of diphenol to be used) can also be used. These are known (see USP 3,419,634), or can be produced by methods known in the literature. Ester-forming monomers can be used in the preparation of polymers containing polycarbonates. Exemplary ester-forming monomers include dicarboxylic acid halides and hydroxycarboxylic acids. Aromatic dicarboxylic acid dihalides used to produce aromatic polyester carbonates can be dichlorides of isophthalic acid, terephthalic acid, diphenyl ether-4,4'-dicarboxylic acid and naphthalene-2,6-dicarboxylic acid. A mixture of dichlorides of isophthalic acid and terephthalic acid in a ratio of about 1:20 to about 20:1 can be used. Phosgene, such as phosgene, can be used together as a difunctional acid derivative in the production process of polyester carbonates. Aromatic polyester carbonates may also contain incorporated hydroxycarboxylic acids. The polyester carbonates may be linear and / or branched. Branching agents have been disclosed above.
[0029] In addition to monophenols, exemplary chain terminators include chlorocarboxylates, and acid chlorides of aromatic monocarboxylic acids, which may optionally be C 1-22 Alkyl or halogen atom substitution, and may also include aliphatic C 2-22 Monocarboxylic acid chlorides. The amount of chain terminator may be from about 0.1 to about 10 mol % relative to the moles of diphenol (in the case of phenolic chain terminators) and relative to the moles of dicarboxylic acid dichloride (in the case of monocarboxylic acid chloride chain terminators).
[0030] Polycarbonate or the copolymer containing carbonate unit can be derived from recycled materials, such as post-consumer recycled materials. Composition can contain up to 95% recycled polycarbonate by composition weight, such as post-consumer recycled materials, about 90% or less by composition weight, or about 80% or less by weight. Composition can contain about 30% by weight or more, about 50% or more, about 75% by weight or more, or about 90% by weight or more recycled polycarbonate based on composition weight. Raw materials as used herein refer to materials that have not been used before. The recycled material can be linear, branched or its mixture. The recycled material can be branched. The recycled material can be in the form of flakes. The recycled material can be recovered from bottles or other structures, wherein the structure used is shredded into flake form. The recycled material can be formed into other structures, such as pellets. Using recycled materials in the form of flakes is the most effective way to utilize the material. The recycled polycarbonate or the copolymer containing carbonate units may contain, for example, 0.1 to 1.0 wt % or 0.1 to 0.25 wt % (based on the recycled polycarbonate or the copolymer containing carbonate units) of impurities such as polyester.
[0031] The composition can contain virgin polycarbonate or the multipolymer containing carbonate units, and its amount is about 5 % by weight or more, about 10 % by weight or more, about 20 % by weight or more, about 30 % by weight or more, or about 40 % by weight or more based on the composition. The composition can contain virgin polycarbonate or the multipolymer containing carbonate units, and its amount is about 65 % by weight or less, about 45 % by weight or less, about 35 % by weight or less, or about 25 % by weight or less based on the composition.
[0032] One or more polymers containing carbonate monomer units may include polycarbonates, copolycarbonates or blends of polycarbonates and copolycarbonates. Polycarbonates and / or copolycarbonates may show a weight average molecular weight sufficient to provide the desired performance for articles prepared from polycarbonates and / or copolycarbonates. The weight average molecular weight of polycarbonates and / or copolycarbonates may be about 5,000 or greater, about 15,000 or greater or about 20,000 or greater. The weight average molecular weight of polycarbonates and / or copolycarbonates may be about 40,000 or less, about 35,000 or less or about 30,000 or less. Unless otherwise indicated, the polycarbonates and / or copolycarbonates herein "molecular weight" refers to the weight average molecular weight (Mw) measured using a laser scattering technique by gel permeation chromatography (GPC) using bisphenol a polycarbonate standards, and is given in grams / mole (g / mole).
[0033] The polycarbonate and / or copolymer used to prepare the disclosed composition may have a melt flow rate that provides the desired processing properties. The melt flow rate may be about 3 or more, about 5 or more, about 10 or more, or about 15 or more. The melt flow rate may be about 30 or less, about 28 or less, about 20 or less, or about 15 or less. A mixture of polycarbonate and / or a copolymer containing carbonate units with different melt flow rates can be used to provide a composite melt flow rate to enhance the processing of the disclosed composition. A mixture of polycarbonate and / or a copolymer containing carbonate units with different melt flow rates may include: a polycarbonate and / or a copolymer containing carbonate units with a low melt flow rate and a polycarbonate and / or a copolymer containing carbonate units with a high melt flow rate. The melt flow rate is determined by measuring the grams of material passing through a capillary with a diameter of 25.4 mm at 300°C and a load of 1.2 kg over a period of 10 minutes. The melt flow rate of the disclosed composition can be about 1 gram / 10 minutes or more, about 3 grams / 10 minutes or more, about 5 grams / 10 minutes or more, 10 grams / 10 minutes or more, or about 15 grams / 10 minutes or more. The melt flow rate of the disclosed composition can be about 70 grams / 10 minutes or less, about 30 grams / 10 minutes or less, about 28 grams / 10 minutes or less, about 22 grams / 10 minutes or less, about 20 grams / 10 minutes or less, or about 10 grams / 10 minutes or less. The melt flow rate of the disclosed composition can be about 3 grams / 10 minutes to about 22 grams / 10 minutes. This test scheme is based on ASTM D1238. The capillary diameter of the plastometer is 9.5504mm and the hole die size is 2.095mm.
[0034] The composition may contain one or more silicon compounds having a branched structure and an organic functional group. Any silicon compound having a branched structure and an organic functional group may be used to enhance the flame retardant properties and mechanical properties of the composition. The organosilicon compound having a branched main chain and an organic functional group may be represented by the following general formula:
[0035]
[0036] Where R 1 , R 2 and R 3 Represents an organic functional group on the main chain, X represents a terminal functional group, and n, m and 1 represent the molar number of a single unit, wherein the organic functional group may include a hydroxyl group, an alkoxy group, an aromatic group or an aromatic group, and a hydrocarbon group (except an aromatic group) may be used as an organic silicon compound.
[0037] The organosilicon compound may contain siloxane units (R 3-0 SiO 2-0.5 ) at least 20 mol% T units (RSiO1.5 ) and / or Q unit (SiO 2.0 ), wherein R represents an organic functional group. At least 20 mol% of the organic functional groups contained in the organosilicon compound can be aromatic groups. The aromatic groups present can be phenyl, biphenyl, naphthalene or their derivatives, or can be phenyl. The side chains other than the phenyl group can be hydrocarbon groups having no more than 4 carbon atoms, or can be methyl groups. The terminal groups can be methyl, phenyl, alkoxy and / or hydroxyl groups. The weight average molecular weight of the organosilicon compound can be 3,000 to 500,000, or 5,000 to 270,000. The amount of the organosilicon compound can be any amount that enhances the flame retardant properties and mechanical properties of the composition. Based on the weight of the composition, the amount of the organosilicon compound can be about 0.01% by weight or more, 0.1% by weight or more, about 0.5% by weight or more, or about 0.5% by weight or more. Based on the weight of the composition, the amount of the organosilicon compound can be about 8.0% by weight or less, about 5.0% by weight or less, about 2.0% by weight or less, or about 1.5% by weight or less.
[0038] The composition may also include a fluorinated anti-drip agent. Anti-drip means that in the event of a fire, the tendency of the composition to form burning drips is reduced. Fluorinated polyolefins known in the art as anti-drip agents can be used in the composition. The anti-drip agent can be a fluoropolymer that forms fibers, and these polymers form a fibril structure in a composition containing polycarbonate. The fluoropolymers that form fibers include polytetrafluoroethylene, tetrafluoroethylene-type copolymers (such as tetrafluoroethylene / hexafluoropropylene copolymers, etc.), partially fluorinated polymers shown in U.S. Patent No. 4,379,910, polycarbonates made from fluorinated diphenols, etc. Polytetrafluoroethylene having a molecular weight of at least 1,000,000, a secondary particle size of at least 100 μm and the ability to form fibrils can be used. Exemplary fluorinated polyolefins are described in EP-A 0 640 655. They are marketed by DuPont under the trade name 30N sales.
[0039] The disclosed composition may contain one or more carbon-based particles, metal or metalloid oxides. Any carbon-based particles, metals or metal oxides that can improve the flame retardancy rating of V0@1.4mm can be used. Exemplary metal or metalloid oxides include Group 3 or Group 4 metal or metalloid oxides. Exemplary metal or metalloid oxides include TiO2, MgO, SiO2, Fe2O3, Al2O3, etc. Exemplary metal or metalloid oxides include TiO2, MgO and SiO2. One or more metal or metalloid oxides can be a mixture of metal and / or metalloid oxides, such as talc containing MgO and SiO2. One or more carbon-based particles can be any particulate carbon material that can improve the flame retardancy of the composition disclosed herein. Exemplary carbon-based particles can be carbon black or carbon nanotubes. One or more carbon compounds, metals or metalloid oxides can be present in an amount sufficient to enhance the flame retardancy of the composition. One or more carbon-based particles, metals or metalloid oxides can be present in an amount sufficient to provide a flame retardancy rating of V0@1.4mm. Based on the weight of the composition, one or more carbon-based particles, metals or metalloid oxides can be present in an amount of about 0.2 wt % or more, about 0.3 wt % or more, or about 0.5 wt % or more. Based on the weight of the composition, one or more carbon-based particles, metals or metal oxides can be present in an amount of about 10 wt % or less, about 5 wt % or less, about 3 wt % or less, or about 2 wt % or less. One or more carbon-based particles, metals or metal oxides can be nanoparticles. The particle size can be any particle size that can improve the flame retardant rating of the composition. The particle size can be about 0.2 micron or more or about 0.35 micron or more. The particle size can be about 2.0 microns or less or about 1.0 microns or less. The particle size can be measured using the laser diffraction technique described in ISO13322. The particle size measured is the average diameter.
[0040] The compositions disclosed herein may contain a buffer system. The buffer system described herein may be a proton-providing (i.e., H + or hydronium ion), accepting protons (i.e., H + or hydronium ions) or any combination of the two. A buffer system can contain a weak acid and a conjugate base. A buffer system can resist changes in pH after the addition of alkaline or acidic components. A buffer system can be based on the total number of protons (i.e., H + or hydronium ion), hydroxyl (i.e. hydroxide or OH -) or both. The buffer system may include one or more monoprotic, diprotic, triprotic or polyprotic buffer compounds. Based on the total weight of the composition, the buffer system can stabilize the polycarbonate in proportion to the total amount of the buffer system present. The buffer system described herein includes one or more buffers having acidic and alkaline functions, so that the pH of the composition can reach about neutral. The buffer system may include one or more buffer compounds, two or more buffer compounds, three or more buffer compounds, or multiple buffer compounds. The buffer system may contain a single compound. The buffer system may contain a pair of compounds. The buffer system may include an inorganic compound, an organic compound, or both. The buffer system may include a counterion. The concentration of the buffer system (i.e., the weight percentage of the total composition) is sufficient to promote the improvement of the molecular weight stability of the polycarbonate. The buffer system may include a buffer compound, which is an inorganic compound or an organic compound, which balances the pH of the composition, thereby achieving optimal copolymerization and compounding. The inorganic compound may include a compound that does not contain saturated carbon (i.e., does not contain a CH bond). The inorganic compound may contain a carbon atom that does not contain a hydrogen bond. The organic compound may include a compound that contains saturated carbon (i.e., contains a CH bond). The buffer compound may include acetate, sulfonate, phosphate, ammonia, formates or any combination thereof. The buffer system may include aromatic or aliphatic buffer compounds. The buffer system may include a buffer compound pair of a weak acid and a conjugate base. The buffer compound may be selected based on an approximately neutral pKa. The buffer compound may control the pH of the water to approximately neutral. The buffer system may include a Good buffer.The organic compound may include 2-(N-morpholino)ethanesulfonic acid (MES), 2-[bis(2-hydroxyethyl)amino]-2-(hydroxymethyl)propane-1,3-diol (bis-trimethylammonium), 2-[(2-amino-2-oxoethyl)-(carboxymethyl)amino]acetic acid (ADA), N-(2-acetylamino)-2-aminoethanesulfonic acid (ACES), piperazine-N,N'-bis(2-ethanesulfonic acid) (PIPES), 2-hydroxy-3-morpholinopropanesulfonic acid (MOPSO), 1,3-bis(tris(hydroxymethyl)methylamino)propane (bis-6-tripropane), NN-bis(2-hydroxyethyl)-2-aminoethanesulfonic acid (BES), MOPS, 2-[[1,3-dihydroxy-2-(hydroxymethyl)propane 1,3-dihydroxy-2-(hydroxymethyl)propan-2-yl]amino]-2-hydroxypropane-1-sulfonic acid (TAPSO), 4-(2-hydroxyethyl)piperazine-1-(2-hydroxypropanesulfonic acid) (HEPPSO), POPSO, 3-[4-(2-hydroxyethyl)piperazine-1-yl]propane-1-sulfonic acid (EPPS or HEPPS), N-(2-hydroxy-1,1-bis(hydroxymethyl)ethyl)glycine (Tr icine), glycylglycine (Gly-Gly), 2-(bis(2-hydroxyethyl)amino)acetic acid (Bic ine), N-(2-hydroxyethyl)piperazine-N′-(4-butanesulfonic acid) (HEPBS), [tris(hydroxymethyl)methylamino]propanesulfonic acid (TAPS), 2-amino-2-methyl-1,3-propanediol (Ammediol or AMPD), N-tris(hydroxymethyl)methyl-4-aminobutanesulfonic acid (TABS), N-(1,1-dimethyl-2-hydroxyethyl)-3-amino-2-hydroxypropanesulfonic acid (AMPSO), N-cyclohexyl-2-aminoethanesulfonic acid (CHES), 3-(cyclohexylamino)-2-hydroxy-1-propanesulfonic acid (CAPSO), 2-amino-2-methylpropan-1-ol (aminomethylpropanol or AMP), N-cyclohexyl-3-aminopropanesulfonic acid (CAPS), 4-(cyclohexylamino)-1-butanesulfonic acid (CABS), or any combination thereof. Inorganic compounds include metal phosphates, metal sulfonates, metal acetates, metal formates and the like.
[0041] The buffer system may include one or more alkali metal phosphates. Any alkali metal phosphate that can enhance the thermal stability of the composition can be used. The alkali metal phosphate can be a sodium metal phosphate or a potassium metal phosphate. Exemplary alkali metal phosphates can be one or more of distearyl pentaerythritol diphosphate, monohydrogen phosphate or dihydrogen phosphate, and monohydrogen phosphate, dihydrogen phosphate or trihydrogen phosphate compounds. Exemplary alkali metal phosphates can be one or more of monohydrogen phosphate, dihydrogen phosphate or trihydrogen phosphate compounds. The alkali metal phosphate can be sodium dihydrogen phosphate. The alkali metal phosphate can be used in any amount to improve the thermal stability of the composition. Based on the weight of the composition, the alkali metal phosphate can be used in any amount of about 0.01% by weight or more, about 0.02% by weight or more, or about 0.03% by weight or more. Based on the weight of the composition, the alkali metal phosphate can be used in any amount of about 1.0% by weight or less, about 0.2% by weight or less, or about 0.1% by weight or less.
[0042] The composition may contain one or more organic metal salts. Any organic metal salt that can function as a carbonizing salt may be used. The one or more organic metal salts may be one or more salts of a perfluoroalkyl sulfur compound or an aromatic sulfur compound. The one or more salts of a perfluoroalkyl sulfur compound may be one or more salts of a perfluoroalkyl sulfur compound. Any salt of a perfluoroalkyl sulfur compound or an aromatic sulfur compound that improves the flame retardancy of the disclosed composition may be used. The one or more salts of a perfluoroalkyl sulfur compound or an aromatic sulfur compound may include one or more alkali metal salts, alkaline earth metal salts, or both. The one or more salts of a perfluoroalkyl sulfur compound or an aromatic sulfur compound may include potassium salts, sodium salts, magnesium salts, calcium salts, or any combination thereof. The one or more salts of a perfluoroalkyl sulfur compound or an aromatic sulfur compound may include one or more potassium salts. The one or more salts of a perfluoroalkyl sulfur compound or an aromatic sulfur compound are salts containing one or more sulfur atoms. The one or more salts of a perfluoroalkyl sulfur compound or an aromatic sulfur compound may be sulfonates. Sulfur-containing salts may include one or more carbon-containing groups. The number of carbon atoms in the sulfur-containing salt may be about 15 or less, about 13 or less, about 7 or less or about 5 or less. The number of carbon atoms in the sulfur-containing salt may be 1 or more, 2 or more, 3 or more or 4 or more. The carbon-containing group may be acyclic or aromatic. The carbon-containing group may include one or more halogen atoms (e.g., fluorine, chlorine, bromine or any combination thereof). The carbon-containing group may include a fluoroalkane (e.g., a perfluoroalkane, such as perfluorobutane, perfluorohexane, perfluoropentane, perfluoroheptane, perfluoropropane or perfluorooctane) with one or more fluorine atoms. The sulfur-containing salt may include one or more potassium perfluoroalkane sulfonates (such as potassium perfluorobutane sulfonate, sodium p-toluene sulfonate or potassium diphenyl sulfone sulfonate), or may be substantially composed of one or more potassium salts. An organic metal salt, such as a perfluoroalkyl metal salt or an aromatic sulfur compound, may be present in a certain amount to improve the flame retardancy of the composition. The organic metal salt may be present in an amount of about 0.05% by weight or more or about 0.1% by weight or more of the composition. The organometallic salt can be present in an amount of about 2.0 wt % or less, about 1.0 wt % or less, about 0.5 wt % or less, about 0.4 wt % or less, or about 0.25 wt % or less of the composition.
[0043] The composition may contain one or more non-halogenated flame retardants commonly used in polycarbonate compositions. Non-halogenated means that there are no halogen atoms in the flame retardant. Using a non-halogenated flame retardant means that the composition containing the non-halogenated flame retardant will not release halogens during combustion. The flame retardant can be any flame retardant known for use in polycarbonate-based compositions that provides flame retardant properties and does not negatively affect the impact, heat resistance, flexural modulus, flexural strength, haze and transparency of the composition. The amount of the flame retardant used can be sufficient to meet the flame retardancy requirements of the end use and is used in an amount that does not adversely affect the performance of the article prepared from the composition. Exemplary flame retardants include phosphorus-containing compounds, such as oligomeric phosphates, poly (block-phosphonooxy-esters) and / or poly (block-phosphonooxy-carbonates), see USP 7,645,850 (incorporated herein in its entirety). Exemplary oligomeric phosphates include bisphenol-A bis (diphenyl phosphate) (BAPP). Exemplary additional flame retardants include 1,3-phenyltetrakis(2,6-dimethylphenyl)ester (Daihachi PX-200).
[0044] The one or more non-halogenated flame retardants may be one or more phosphazenes. Any one or more phosphazenes that enhance flame retardancy may be used. The phosphazene may contain more than one phosphazene unit. Phosphazene is an organic compound having a -P=N- structure. The phosphazene may be a linear structure containing one or more phosphazene units, or a cyclic structure containing one or more phosphazene units. The phosphorus atom on the phosphazene structure may be combined with one or more hydrocarbonoxy structures. The hydrocarbonoxy group may be an alkoxy, an aryloxy group, an alkyl-substituted aryloxy group, an alkoxy-substituted aryloxy group, or a halogen-substituted aryloxy group. The hydrocarbonoxy group may be an aryloxy group or an alkyl-substituted aryloxy group. The hydrocarbonoxy group may be a phenoxyoxy group or an alkyl-substituted phenoxy group. The alkyl group may be C 1-10 Alkyl, C 1-3Alkyl or methyl or ethyl. The cyclic phosphazene compound may contain 1 or more phosphazene units, and may also contain 3 or more phosphazene units. The cyclic phosphazene compound may contain 25 or less phosphazene units, 10 or less phosphazene units, or 5 or less phosphazene units. The linear phosphazene compound may contain 1 or more phosphazene units, 3 or more phosphazene units, 5 or more phosphazene units, or 6 or more phosphazene units. The linear phosphazene compound may contain 10,000 or less phosphazene units, 1,000 or less phosphazene units, 100 or less phosphazene units, or 25 or less phosphazene units. Exemplary cyclic phosphazenes include phenoxycyclotriphosphazenes, octaphenoxycyclotetraphosphazenes, and decaphenoxycyclopentaphosphazenes. Cyclic phosphazenes can be obtained by reacting ammonium chloride with phosphorus pentachloride at 120 to 130°C to obtain a mixture containing cyclic and linear chlorophosphazenes, extracting cyclic chlorophosphazenes such as hexachlorocyclotriphosphazenes, octachlorocyclotetraphosphazenes, and decachlorocyclopentaphosphazenes, and then replacing them with phenoxy groups. Exemplary linear phosphazenes include compounds obtained by the following method: ring-opening polymerization of the hexachlorocyclotriphosphazene obtained by the above method at 220-250°C, and then replacing the chain dichlorophosphazenes with a degree of polymerization of 3-10,000 (or as described above) obtained therefrom with phenoxy groups. The phosphazene compound can be cross-linked. The phosphazene compound can be cross-linked by bisphenol compounds such as 4,4'-diphenylene groups, such as 4,4'-sulfonyldiphenylene (bisphenol S residue), 2,2-(4,4'-diphenylene), isopropylidene groups, 4,4'-oxydiphenylene groups, 4,4'-thiodiphenylene groups, and the like. The cross-linked phenoxyphosphazene compound generally has a phenylene content of 50-99.9 wt % or 70-90 wt %. The cross-linked phenoxyphosphazene compound may not contain any free hydroxyl groups in the molecule.
[0045] Based on the weight of the composition comprising polycarbonate and / or the copolymer containing carbonate units, one or more flame retardants can be present in an amount of about 0.1 wt % or more, about 1 wt % or more, or about 5 wt % or more.Based on the weight of the composition, one or more flame retardants can be present in an amount of about 30 wt % or less, about 20 wt % or less, or about 10 wt % or less.
[0046] The disclosed compositions contain one or more antioxidants. The antioxidants may be introduced into the composition from the ingredients used (e.g., impact modifiers). The antioxidants may be added to the composition separately.
[0047] The antioxidant may be one or more of phenol, phosphorus, hydroquinone and alkylated hydroquinones, tocopherol, O- and N-benzyl compounds, alkylene bisphenols, hydroxybenzylated malonates, aromatic hydroxybenzyl compounds, triazine compounds, benzyl phosphonates, acylaminophenols, esters and amides of propionic acid, ascorbic acid or amine-based antioxidants. The antioxidant may be one or more of phenol, phosphorus, hydroquinone and alkylated hydroquinones, tocopherol, O- and N-benzyl compounds, alkylene bisphenols, hydroxybenzylated malonates, aromatic hydroxybenzyl compounds, triazine compounds, benzyl phosphonates, acylaminophenols, esters and amides of propionic acid, ascorbic acid or amine-based antioxidants. The antioxidant may be one or more phenol-based compounds, and the phenol-based antioxidants include 2,6-di-tert-butyl-4-methylphenol; 2,6-diphenyl-4-methoxyphenol; 2,2′-methylenebis(6-tert-butyl-4-methylphenol); 2,2′-methylenebis(6-tert-butyl-4-methylphenol); 2,2′-methylenebis[4-methyl-6-(α-methylcyclohexyl)phenol]; 1,1-bis(5-tert-butyl-4-hydroxy-2-methylphenyl)butane; 2,2′-methylenebis(4-methyl-6-cyclohexyl)phenol; 1,1,3-Tris(5-tert-butyl-4-hydroxy-2-methylphenyl)butane; 2,2-Bis(5-tert-butyl-4-hydroxy-2-methylphenyl)-4-n-dodecylmercaptobutane; Ethylene glycol bis[3,3-bis(3-tert-butyl-4-hydroxyphenyl)butyrate]; 1,1-Bis(3,5-dimethyl-2-hydroxyphenyl)-3-(n-dodecylthio)butane; 4,4′-thiobis(6-tert-butyl-3-methylphenol); 1,3, 5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-2,4,6-trimethylbenzene; distearyl 2,2-bis(3,5-di-tert-butyl-4-hydroxybenzyl)malonate; n-octadecyl-3-(4-hydroxy-3,5-di-tert-butylphenyl)propionate; tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane; and pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate. Antioxidants based on hydroquinone and alkylated hydroquinone include 2,6-di-tert-butyl-4-methoxy The antioxidants include 2,5-di-tert-butylhydroquinone, 2,5-di-tert-amylhydroquinone, 2,6-diphenyl-4-octadecyloxyphenol, 2,6-di-tert-butylhydroquinone, 2,5-di-tert-butyl-4-hydroxyanisole, 3,5-di-tert-butyl-4-hydroxyanisole, 3,5-di-tert-butyl-4-hydroxyphenyl stearate, bis(3,5-di-tert-butyl-4-hydroxyphenyl) adipate. Tocopherol-based antioxidants include α-tocopherol, β-tocopherol, γ-tocopherol, δ-tocopherol and mixtures thereof (vitamin E).Antioxidants based on O- and N-benzyl compounds include, for example, 3,5,3′,5′-tetra-tert-butyl-4,4′-dihydroxydibenzyl ether, tris(3,5-di-tert-butyl-4-hydroxybenzyl)amine. Antioxidants based on alkylene bisphenols include: 2,2′-methylenebis(6-tert-butyl-4-methylphenol), 2,2′-methylenebis(6-tert-butyl-4-ethylphenol), 2,2′-methylenebis[4-methyl-6-(α-methylcyclohexyl)phenol], 2,2′-methylenebis(4-methyl-6-cyclohexylphenol), 2,2′-methylenebis(6-nonyl-4-methylphenol), 2,2'-methylenebis(4,6-di-tert-butylphenol), 2,2'-ethylenebis(4,6-di-tert-butylphenol), 2,2'-ethylenebis(6-tert-butyl-4-isobutylphenol), 2,2'-methylenebis[6-(α-methylbenzyl)-4-nonylphenol], 2,2'-methylenebis[6-(α,α-dimethylbenzyl)-4-nonylphenol], 4,4'-methylenebis(2 ,6-di-tert-butylphenol), 4,4′-methylenebis(6-tert-butyl-2-methylphenol), 1,1-bis(5-tert-butyl-4-hydroxy-2-methylphenyl)butane, 2,6-bis(3-tert-butyl-5-methyl-2-hydroxybenzyl)-4-methylphenol, 1,1,3-tri(5-tert-butyl-4-hydroxy-2-methylphenyl)butane, ethylene glycol bis[3,3-bis(3′-tert-butyl- The antioxidants based on hydroxybenzylated malonate include dioctadecyl-2,2-bis(3,5-di-tert-butyl-2-hydroxybenzyl)malonate, dioctadecyl-2-(3-tert-butyl-4-hydroxy-5-methylbenzyl)malonate, bis[4-(1,1,3,3-tetramethylbutyl)phenyl]-2,2-bis(3,5-di-tert-butyl-4-hydroxybenzyl)malonate. Aromatic hydroxybenzyl-based antioxidants include 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-2,4,6-trimethylbenzene, 1,4-bis(3,5-di-tert-butyl-4-hydroxybenzyl)-2,3,5,6-tetramethylbenzene, and 2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)phenol.The antioxidants based on triazine compounds include 2,4-bis(octylmercapto)-6-(3,5-di-tert-butyl-4-hydroxyanilino)-1,3,5-triazine, 2-octylmercapto-4,6-bis(3,5-di-tert-butyl-4-hydroxyanilino)-1,3,5-triazine, 2-octylmercapto-4,6-bis(3,5-di-tert-butyl-4-hydroxyphenoxy)-1,3,5-triazine, 2,4,6-tris-(3,5-di-tert-butyl- isocyanurate, 2,4,6-tris(3,5-di-tert-butyl-4-hydroxyphenylethyl)-1,3,5-triazine, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxyphenylpropionyl)-hexahydro-1,3,5-triazine and 1,3,5-tris(3,5-dicyclohexyl-4-hydroxybenzyl) isocyanurate. Benzylphosphonate-based antioxidants include dimethyl-2,5-di-tert-butyl-4-hydroxybenzylphosphonate, diethyl-3,5-di-tert-butyl-4-hydroxybenzylphosphonate, dioctadecyl-3,5-di-tert-butyl-4-hydroxybenzylphosphonate, dioctadecyl-5-tert-butyl-4-hydroxy-3-methylbenzylphosphonate, and the calcium salt of 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid monoethyl ester. Acylaminophenol-based antioxidants include, for example, 4-hydroxylauroylanilide, 4-hydroxystearylanilide, and octyl N-(3,5-di-tert-butyl-4-hydroxyphenyl)carbamate. Exemplary antioxidants include esters of D-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid with monohydric or polyhydric alcohols (e.g., methanol, ethanol, n-octanol, isooctyl alcohol, octadecanol, 1,6-hexanediol, 1,9-nonanediol, ethylene glycol, 1,2-propylene glycol, neopentyl glycol, thiodiethylene glycol, diethylene glycol, triethylene glycol, pentaerythritol), tris(hydroxyethyl)isocyanurate, N,N'-bis(hydroxyethyl)oxamide, 3-thioundecanol, 3-thiopentadecanol, trimethylhexanediol, trimethylolpropane, 4-hydroxymethyl-1-phospha-2,6,7-trioxabicyclo[2.2.2]octane. Exemplary antioxidants include esters of β-(5-tert-butyl-4-hydroxy-3-methylphenyl)propionic acid with monohydric or polyhydric alcohols (e.g., methanol, ethanol, n-octanol, isooctyl alcohol, octadecanol, 1,6-hexanediol, 1,9-nonanediol, ethylene glycol, 1,2-propylene glycol, neopentyl glycol, thiodiethylene glycol, diethylene glycol, triethylene glycol, pentaerythritol), tris(hydroxyethyl)isocyanurate, N,N′-bis ... ethyl)oxalamide, 3-thioundecanol, 3-thiopentadecanol, trimethyl hexanediol, trimethylolpropane, 4-hydroxymethyl-1-phospha-2,6,7-trioxabicyclo[2.2.2]octane; 3,9-bis[2-{3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5.5]-undecane.Exemplary antioxidants include esters of β-(3,5-dicyclohexyl-4-hydroxyphenyl)propionic acid with monohydric or polyhydric alcohols (e.g., methanol, ethanol, octanol, octadecanol, 1,6-hexanediol, 1,9-nonanediol, ethylene glycol, 1,2-propylene glycol, neopentyl glycol, thiodiethylene glycol, diethylene glycol, triethylene glycol, pentaerythritol), tris(hydroxyethyl)isocyanurate, N,N'-bis(hydroxyethyl)oxamide, 3-thioundecanol, 3-thiopentadecanol, trimethylhexanediol, trimethylolpropane, 4-hydroxymethyl-1-phospha-2,6,7-trioxabicyclo[2.2.2]octane. Exemplary antioxidants include esters of 3,5-di-tert-butyl-4-hydroxyphenylacetic acid with monohydric or polyhydric alcohols (e.g., methanol, ethanol, octanol, octadecanol, 1,6-hexanediol, 1,9-nonanediol, ethylene glycol, 1,2-propylene glycol, neopentyl glycol, thiodiethylene glycol, diethylene glycol, triethylene glycol, pentaerythritol), tris(hydroxyethyl)isocyanurate, N,N′-bis(hydroxyethyl)oxamide, 3-thioundecanol, 3-thiopentadecanol, trimethylhexanediol, trimethylolpropane, 4-hydroxymethyl-1-phospha-2,6,7-trioxabicyclo[2.2.2]octane. Exemplary antioxidants include amides of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, such as N,N′-bis(3,5-di-tert-butyl-4-hydroxyphenylpropionyl)hexamethylene diamide, N,N′-bis(3,5-di-tert-butyl-4-hydroxyphenylpropionyl)trimethylene diamide, N,N′-bis(3,5-di-tert-butyl-4-hydroxyphenylpropionyl)hydrazide, N,N′-bis[2-(3-[3,5-di-tert-butyl-4-hydroxyphenyl]propionyloxy)ethyl]oxalamide (. XL-1, provided by Uniroyal). An exemplary antioxidant is ascorbic acid (vitamin C). Amine antioxidants include N,N′-diisopropyl-p-phenylenediamine, N,N′-di-sec-butyl-p-phenylenediamine, N,N′-bis(1,4-dimethylpentyl)-p-phenylenediamine, N,N′-bis(1-ethyl-3-methylpentyl)-p-phenylenediamine, N,N′-bis(1-methylheptyl)-p-phenylenediamine, N,N′-dicyclohexyl-p-phenylenediamine, N,N′-diphenyl-p-phenylenediamine, N,N′-bis(2-naphthyl)-p-phenylenediamine, N-isopropyl-N′-phenyl-p-phenylenediamine, N-(1,3-dimethylbutyl)-N′-phenyl-p-phenylenediamine, N-( 1-methylheptyl)-N'-phenyl-p-phenylenediamine, N-cyclohexyl-N'-phenyl-p-phenylenediamine, N,N'-dimethyl-N,N'-di-sec-butyl-p-phenylenediamine, diphenylamine, N-allyl diphenylamine, 4-isopropoxy diphenylamine, N-phenyl-1-naphthylamine, N-(4-tert-octylphenyl)-1-naphthylamine, N-phenyl-2-naphthylamine, octylated diphenylamine, p,p'-di-tert-octyl diphenylamine, 4-n-butylaminophenol, 4-butyrylaminophenol, 4-nonanoylaminophenol, 4-dodecylaminophenol, 4-octadecanoylaminophenol, bis(4 -methoxyphenyl)amine, 2,6-di-tert-butyl-4-dimethylaminomethylphenol, 2,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, N,N,N',N'-tetramethyl-4,4'-diaminodiphenylethane, 1,2-bis[(2-methylphenyl)amino]ethane, 1,2-bis(phenylamino)propane, (o-tolyl)biguanide, bis[4-(1',3'-dimethylbutyl)phenyl]amine, tert-octylated N-phenyl-1-naphthylamine, mixtures of mono- and di-alkylated tert-butyl / tert-octyl diphenylamines, mono- and di-alkylated mixture of monoalkylated nonyldiphenylamine, mixture of monoalkylated and dialkylated dodecyldiphenylamine, mixture of monoalkylated and dialkylated isopropyl / isohexyldiphenylamine, mixture of monoalkylated and dialkylated tert-butyldiphenylamine, N,N,N′,N′-tetraphenyl-1,4-diaminobut-2-ene, N,N-bis(2,2,6,6-tetramethylpiperidin-4-yl-hexamethylenediamine, bis(2,2,6,6-tetramethylpiperidin-4-yl)sebacate, 2,2,6,6-tetramethylpiperidin-4-one, 2,2,6,6-tetramethylpiperidin-4-ol.Phosphorus antioxidants include tetrakis(2,4-di-tert-butylphenyl)-4,4-biphenylene phosphite, tris(2,4-di-tert-butylphenyl)phosphite, 2,2'-methylenebis(4,6-di-tert-butylphenyl)octylphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, di(nonylphenyl)pentaerythritol diphosphite, phenyl-bisphenol A-pentaerythritol diphosphite, distearyl pentaerythritol diphosphite, dioctyl pentaerythritol diphosphite, dilauryl pentaerythritol diphosphite, Phosphites, diphenyl pentaerythritol diphosphites, dicyclohexyl pentaerythritol diphosphites, bis(2,4,6-tri-tert-butylphenyl)pentaerythritol diphosphites, 2,2'-ethylenebis(4,6-di-tert-butylphenyl)fluorophosphites, triisodecylphosphites, tridodecylphosphites, phenylisooctylphosphites, phenylisodecylphosphites, phenyldodecylphosphites, diphenylisooctylphosphites, diphenylisodecylphosphites, diphenyldodecylphosphites, triphenylphosphites, tri(monononylphenyl)phosphites and tri(dinononylphenyl)phosphites. The antioxidant may be octadecyl 3,5-di-(tert-)-butyl-4-hydroxyhydrocinnamate, which may be commercially available as IRGANOX 1076 from BASF.
[0048] Exemplary antioxidant additives include, for example, organic phosphites such as tris(nonylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite (e.g., "IRGAFOS 168" or "I-168"), bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, distearylpentaerythritol diphosphite, and the like; alkylated monophenols or polyphenols; alkylation reaction products of polyphenols with dienes, such as tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)methane, and the like; butylation reaction products of p-cresol or dicyclopentadiene; alkylated hydroquinones; hydroxylated thiodiphenyl ethers; alkylidene-bisphenols; benzyl compounds; reactions of β-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid with monohydric or polyhydric alcohols; Esters; esters of β-(5-tert-butyl-4-hydroxy-3-methylphenyl)-propionic acid and monohydric or polyhydric alcohols; esters of thioalkyl or thioaryl compounds, such as distearyl thiopropionate, dilauryl thiopropionate, ditridecyl thiodipropionate, octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, pentaerythritol-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, etc.; amides of β-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, etc., or a combination comprising at least one of the foregoing antioxidants.
[0049] Antioxidants can be present in any amount in the composition and the structures formed therefrom to retard oxidation of the polymer. Based on the weight of the disclosed composition, the antioxidant can be present in an amount of about 100 parts per million or greater, about 200 parts per million or greater, about 300 parts per million or greater, about 500 parts per million or greater, or about 1000 parts per million or greater. Based on the weight of the disclosed composition, the antioxidant can be present in an amount of about 10,000 parts per million or less, about 8,000 parts per million or less, or about 6,000 parts per million or less.
[0050] The composition may contain a release agent. Exemplary release agents include any release agent known in the art and combinations thereof. The release agent may be an internal release agent. The release agent may include one or more compatibilizers, such as those taught in now expired U.S. Pat. No. 5,212,209A, which is incorporated herein by reference in its entirety for all purposes. Example classes of release agents include aliphatic carboxylic acids; esters of aliphatic carboxylic acids and alcohols; aliphatic hydrocarbon compounds having a number average molecular weight of 200 to 15,000; and polysiloxane-based silicone oils. Examples of aliphatic carboxylic acids include saturated or unsaturated aliphatic monovalent, divalent or trivalent carboxylic acids. Aliphatic carboxylic acids also include alicyclic carboxylic acids. The aliphatic carboxylic acid may be a C 6-36 The aliphatic carboxylic acid may be a monovalent or divalent carboxylic acid. 6-36Aliphatic saturated monovalent carboxylic acids. Specific examples of such aliphatic carboxylic acids include palmitic acid, stearic acid, caproic acid, capric acid, lauric acid, arachidic acid, behenic acid, lignoceric acid, cerotic acid, melissic acid, tetratriadecanoic acid, montanic acid, adipic acid and azelaic acid. Examples of aliphatic carboxylic acids in esters of aliphatic carboxylic acids and alcohols include the same aliphatic carboxylic acids as described above. Examples of alcohols include saturated or unsaturated, monohydric or polyhydric alcohols, which may have substituents, such as fluorine atoms or aromatic groups. The alcohol may be a monohydric or polyhydric saturated alcohol having a carbon number of no more than 30. The alcohol may be an aliphatic saturated monohydric alcohol and an aliphatic saturated polyhydric alcohol having a carbon number of no more than 30. The term "aliphatic" is used herein as a term that also includes alicyclic compounds. Specific examples of such alcohols include octanol, decyl alcohol, dodecanol, stearyl alcohol, behenyl alcohol, ethylene glycol, diethylene glycol, glycerol, pentaerythritol, 2,2-dihydroxy perfluoropropanol, neopentyl glycol, ditrimethylolpropane and dipentaerythritol. Each of the above esters can be pure or a mixture of multiple compounds. Each of the aliphatic carboxylic acid and alcohol that are combined to form an ester can be a single type, or two or more types can be used in any combination in any proportion. Specific examples of esters of aliphatic carboxylic acids and alcohols include beeswax (a mixture containing lauryl palmitate as a main component), stearyl stearate, behenyl behenate, stearyl behenate, glyceryl monopalmitate, glyceryl monostearate, glyceryl distearate, glyceryl tristearate, pentaerythritol monopalmitate, pentaerythritol monostearate, pentaerythritol distearate, pentaerythritol tristearate and pentaerythritol tetrastearate. Examples of aliphatic hydrocarbons having a number average molecular weight of 200-15,000 include liquid paraffin, paraffin wax, microcrystalline wax, polyethylene wax, Fischer-Tropsch wax, and α-olefin oligomers having a carbon number of 3-12. Aliphatic hydrocarbons also include alicyclic hydrocarbons. Each of these hydrocarbons can be partially oxidized. Aliphatic hydrocarbons can be paraffin wax, polyethylene wax, and partially oxidized polyethylene wax is preferred. More preferred are paraffin wax and polyethylene wax. The number average molecular weight of aliphatic hydrocarbons must not exceed 5000. Examples of polysiloxane-based silicone oils include dimethyl silicone oil, methylphenyl silicone oil, diphenyl silicone oil, and fluorinated alkyl silicone oil. A single type of release agent may be included, or two or more types of release agents may be included in any combination of any proportion.
[0051] The amount of the release agent is not limited, and may be about 0.001 wt % or more, about 0.01 wt % or more, or about 0.1 wt % or more based on the composition. The amount of the release agent is not limited, and may be about 2 wt % or less, about 1 wt % or less, or about 0.6 wt % or less based on the weight of the composition. If the content of the release agent is below the lower limit of the range, the demolding effect may be insufficient, and on the other hand, if the content of the release agent exceeds the upper limit of the range, a decrease in hydrolysis resistance, mold contamination during injection molding, and the like may occur.
[0052] The composition may contain one or more impact modifiers. The terms impact modifier and rubber are used interchangeably. Various impact modifiers can be used in the disclosed composition; such as diene rubber, ethylene propylene rubber, ethylene propylene diene (EPDM) rubber, ethylene copolymer rubber, acrylate rubber, polyisoprene rubber, silicone rubber, silicone-acrylate rubber, polyurethane, thermoplastic elastomer, halogen-containing rubber, and mixtures thereof. Also suitable are interpolymers of rubber-forming monomers and other copolymerizable monomers. The rubber may be present in a sufficient amount in the formulated composition to provide the composition with the desired impact properties. The desired impact properties include increased izod, charpy, gardner, stretching, falling dart, etc. The composition, as used in the present context, is a formulated composition containing all ingredients for the intended use.
[0053] The rubber can be a diene rubber such as polybutadiene, polyisoprene, polypentadiene, polychloroprene, etc. or a mixture of diene rubbers, i.e., any rubbery polymer of one or more conjugated 1,3-dienes such as 1,3-butadiene. Such rubbers include homopolymers of 1,3-butadiene and copolymers of 1,3-butadiene with one or more copolymerizable monomers such as vinylidene-substituted aromatic compounds (styrene). The diene rubber can be a homopolymer of 1,3-butadiene. Exemplary copolymers of 1,3-butadiene are blocks or tapered block rubbers of at least about 30% by weight of 1,3-butadiene, about 50% by weight, about 70% by weight, or about 90% by weight of 1,3-butadiene and up to about 70% by weight of vinylidene-substituted aromatic monomers, up to about 50% by weight, up to about 30% by weight, or up to about 10% by weight of vinylidene-substituted aromatic monomers, the weight being based on the weight of the 1,3-butadiene copolymer.
[0054] The impact modifier used may be those polymers and copolymers that exhibit a secondary transition temperature (sometimes referred to as a glass transition temperature (Tg)) of no greater than 0°C or no greater than -20°C for the diene segment, as determined using conventional techniques (e.g., ASTM test method D 746-52T). Tg is the temperature or temperature range at which a polymer material exhibits an abrupt change in its physical properties, including, for example, mechanical strength. Tg may be determined by differential scanning calorimetry (DSC). The diene rubber may have a cis content equal to or less than 99% or less than 97%. The cis content of the diene rubber may be equal to or greater than 20% or greater than 37%, wherein the cis weight percentage is based on the weight of the diene rubber. The rubber may be a 1,3-butadiene rubber having at least about 1% by weight of 1,2-vinyl or at least about 7% by weight of 1,2-vinyl based on the weight of the 1,3-butadiene rubber. The 1,3-butadiene rubber may have less than or equal to about 30% by weight of 1,2-vinyl or less than or equal to about 13% by weight of 1,2-vinyl based on the weight of the 1,3-butadiene rubber. The diene rubber may have a weight average molecular weight of at least about 100 kilograms per mole (kg / mol) or a weight average molecular weight of at least about 300 kg / mol. The diene rubber may have a weight average molecular weight equal to or less than about 900 kg / mol or a weight average molecular weight equal to or less than 600 kg / mol. The diene rubber has a solution viscosity of at least 10 centistokes (cSt) (ten percent (10%) solution in styrene) or a solution viscosity of about 30 cSt. The diene rubber may have a solution viscosity equal to or less than about 500 cSt or equal to or less than about 400 cSt. The rubber with the grafted and / or occluded polymer (if present) is dispersed in the continuous matrix phase in the form of discrete particles. The rubber particles may include a range of sizes having a unimodal, bimodal or multimodal distribution. The average particle size of the rubber particles used herein refers to the volume average diameter. The volume average diameter of a group of particles can be the same as the weight average diameter. The average particle diameter measurement generally includes the polymer grafted to the rubber particles and the occlusion of the polymer within the particles. Unless otherwise indicated, the rubber particle sizes disclosed and claimed herein are those having an ACCUCOMP TMThe Coulter Multisizer II or II e with software version 2.01 is measured by the following method: about 3 polymer sample pellets (30-70 mg) are dissolved in 5 milliliters (ml) of dimethylformamide (DMF) by stirring for about 15 minutes to 20 minutes using an ultrasonic bath. 10 ml of electrolyte solution (DMF containing 1% NH4SCN) is mixed with 0.2 ml of sample solution. The plow measuring table is used with a 20-micron Coulter tube and a 1.16-micron calibration material. The coincidence level indicator reading of the device should be between 5% and 10%. If the reading is higher than 10%, dilute the sample with electrolyte solution in a beaker, or if the reading is too low, add more drops of polymer solution in DMF. The volume average particle size is reported. The average particle size of the rubber particles may be equal to or greater than about 0.05 microns (micrometers) (μm), equal to or greater than about 0.1 microns, and equal to or greater than about 0.5 microns. The rubber particles may have an average particle size diameter of about 10 microns or less, about 5 microns or less, or about 4 microns or less.
[0055] The impact modifier may be an impact modifier (MBS) based on butadiene or styrene-butadiene rubber and methyl methacrylate-styrene grafted with a core-shell structure, a silicone-acrylate rubber with a core-shell structure, a core-shell impact modifier based on acrylate rubber, etc. The core-shell impact modifier based on butadiene or styrene-butadiene rubber is an impact modifier based on butadiene or styrene-butadiene rubber grafted with methyl methacrylate or methyl methacrylate-styrene copolymer, such as Kane Ace M732 purchased from Kaneka Japan, Paraloid 100 purchased from Dow Chemicals, etc. TM EXL2650J, EXL2690, EXL2691J, etc. The silicone acrylate rubber having a core-shell structure can be made from alkyl methacrylate and / or alkyl acrylate, a crosslinking agent, and a grafting agent. Exemplary alkyl methacrylate and / or alkyl acrylate are C 1-5 - alkyl esters, such as methyl, ethyl, n-butyl, tert-butyl, n-propyl, n-hexyl, n-octyl, n-lauryl and 2-ethylhexyl esters; haloalkyl esters, preferably haloC 1-5-alkyl esters, such as chloroethyl acrylate, and mixtures of these monomers. Particularly preferred is n-butyl acrylate. Monomers having more than one polymerizable double bond can be used as crosslinking agents for the polyalkyl (meth) acrylate rubber component of the silicone acrylate rubber. Examples of crosslinking monomers are esters of unsaturated monocarboxylic acids having 3 to 8 carbon atoms and unsaturated monohydric alcohols having 3 to 12 carbon atoms or saturated polyols having 2 to 4 OH- groups and 2 to 20 carbon atoms, such as ethylene glycol dimethacrylate, propylene glycol dimethacrylate, 1,3-butanediol dimethacrylate and 1,4-butanediol dimethacrylate. Such crosslinking agents can be used alone or as a mixture of at least two crosslinking agents. Exemplary grafting agents are allyl methacrylate, triallyl cyanurate, triallyl isocyanurate or mixtures thereof. Allyl methacrylate can also be used as a crosslinking agent. Such grafting agents can be used alone or as a mixture of at least two grafting agents. Based on the total weight of the polyalkyl (meth) acrylate rubber component of the silicone acrylate rubber, the crosslinking agent and the grafting agent may be present in an amount of about 0.1 wt % to about 20 wt %. Exemplary silicone acrylate rubbers include, for example, Metablen S-2100, S-2001, S-2006, etc. available from Mitsubishi Rayon. The composition may include a silicone-acrylate rubber impact modifier, preferably in an amount of 1 wt % to 8 wt %, more preferably 1 wt % to 6 wt %, and particularly preferably 2.0 wt % to 5.0 wt %, based on the total weight of the composition. Exemplary acrylate rubber-based core-shell impact modifiers are acrylate rubber-based impact modifiers grafted with methyl methacrylate, including Paraloid available from Dow. TM EXL2311, EXL2313, EXL2315, EXL2300, EXL2330, and EXL2390; and from Arkema 410, 440 and 480. The compositions disclosed herein contain an impact modifier (rubber) in an amount of about 0.5 wt % or more, about 1.0 wt % or more, or about 2.0 wt % or more, based on the weight of the composition. The compositions disclosed herein contain an impact modifier in an amount of about 8 wt % or less, about 6 wt % or less, about 6 wt % or less, about 30 wt % or less, about 5 wt % or less, or about 2.5 wt % or less, based on the weight of the composition. The impact modifier may contain about 90 wt % of the polydiene or about 99 wt % of the polydiene.
[0056] Compositions disclosed herein may include UV absorbers (i.e., UV stabilizers), which in another embodiment play a role in stabilizing the color of the composition. When adding UV absorbers, polycarbonate, vinylidene-substituted aromatic compounds, or both may absorb light energy in ultraviolet rays as heat. UV absorbers can reduce the weathering of polymer compositions (e.g., compositions of polycarbonate and vinylidene-substituted aromatic compounds). UV absorbers can include benzotriazole, hydroxyphenyl triazine, benzophenone, s-triazine, etc., or any combination thereof. UV absorbers can exist in an amount of about 500ppm or more, about 1,000ppm or more, or about 1,500ppm or more. UV absorbers can exist in an amount of about 10,000ppm or less, about 8,000ppm or less, or about 6,000ppm or less. UV absorbers can exist in an amount of about 500ppm to about 10,000ppm.
[0057] If used, filler can be reinforcing filler, for example length-to-diameter ratio is about 4 or larger fiber. Based on the gross weight of polymer composition, the amount of other fillers (for example non-reinforcing filler, for example talcum, clay etc.) can be about 6 % by weight or less, about 4 % by weight or less, about 2 % by weight or less or about 1 % by weight or less. Reinforcing filler can be adopted to improve the intensity of polymer composition and / or reduce the linear thermal expansion coefficient of composition. Reinforcing filler can comprise glass fiber, carbon fiber, metal fiber or their combination in any. Other reinforcing fillers comprise mineral fillers with needle-like structure (i.e. needle-like structure), for example wollastonite.
[0058] The composition may optionally include a component that adsorbs volatile organic compounds. The component may be zeolite, activated carbon, bamboo, charcoal, or a combination thereof.
[0059] The disclosed compositions may contain one or more additives commonly used in compositions of this type. Exemplary additives include: zinc salts, colorants, mold release agents, fillers, reinforcing fibers, flame retardant additives, stabilizers, adsorbents (e.g., zeolites, activated carbon, bamboo charcoal, etc.), antistatic agents, silicone oils, flow enhancers, etc. Exemplary anti-ignition additives include halogenated hydrocarbons, halogenated carbonate oligomers, halogenated diglycidyl ethers, organophosphorus compounds, fluorinated olefins, antimony oxides, and metal salts of aromatic sulfur, or mixtures thereof may be used. Compounds that stabilize the rubber-modified vinylidene-substituted aromatic copolymer compositions to prevent degradation caused by, but not limited to, heat, light, and oxygen, or mixtures thereof may be used. Fillers and reinforcing agents may also be present. Exemplary fillers include talc, clay, wollastonite, mica, glass, or mixtures thereof. Some of these additives may adsorb volatile organic compounds, such as zeolites, activated carbon, bamboo charcoal, etc.
[0060] The additive and / or filler and / or adsorbent may be present in the formulated composition in an amount of about 0.01 % by weight or more, about 0.1 % by weight or more, about 1 % by weight or more, about 2 % by weight or more, or about 3 % by weight or more, based on the weight of the composition. The additive and / or filler may be present in an amount of about 40 % by weight or less, about 30 % by weight or less, about 20 % by weight or less, about 15 % by weight or less, about 10 % by weight or less, about 5 % by weight or less, based on the weight of the composition. Based on the weight of the composition, additives and adsorbents may be present independently in an amount of up to 5 % by weight, and fillers may be present in an amount of up to about 40 % by weight.
[0061] The disclosed compositions can be produced by mixing the components in a known manner and melt mixing and / or melt extruding them at temperatures of 200° C. to 300° C. in conventional units such as internal kneaders, extruders and twin-screw extruders. The individual components can be mixed continuously and simultaneously in a known manner at temperatures of about 23° C. (room temperature) and above. In the case of a twin-screw extruder, the coated particles can be added after the first set of screws, i.e. after the kneading screws.
[0062] The disclosed compositions can be molded using methods known in the art. The polycarbonate compositions can be molded into useful molded articles by various means, such as injection molding, overmolding, extrusion, rotational molding, blow molding, and thermoforming to form various molded articles. Such articles may include thin-walled articles for consumer products (such as mobile phones, MP3 players, computers, laptops, cameras, video recorders, electronic tablets, handheld receivers, kitchen appliances, electrical housings, etc.), such as smart meter housings, etc.; electrical connectors, lighting equipment components, decorations, household appliances, roofs, greenhouses, sunrooms, swimming pool fences, light-emitting diodes (LEDs) and light panels, extruded film and sheet products; electrical components, such as relays; and telecommunications components, such as components of base station terminals. The present disclosure also contemplates additional manufacturing operations for the articles, such as but not limited to molding, in-mold decoration, baking in a paint oven, lamination, and / or thermoforming. The disclosed composition is heated to a temperature at which the composition flows, which temperature may be higher than the glass transition temperature of the polycarbonate in the composition. Such temperatures may be above 155°C, above 200°C or more, 250°C or more. Such temperatures may be 400°C or less, or 300°C or less. The mold may be heated to facilitate processing, such as to 60°C or more, 80°C or more, or 100°C or more.
[0063] The UL-94 vertical test (20mm vertical burning test) in the UL standard is a measurement method for measuring the flame retardancy index of unexpanded resins. The purpose of the test is to determine the resistance of plastic materials used for components in equipment and appliances to the spread of flames and luminous light. UL 94 is used to measure the burning rate and characteristics based on standard samples. The sample size is 12.7mm x 127mm with different thicknesses. When giving a rating, the thickness must be reported. The relevant ratings are: V-2, V-1, and V-0. "V-0" is the most common rated visible component where increased combustion protection is required. V-0 has the following requirements:
[0064] 1. None of the five samples burned for more than 10 seconds after each of two 10-second flame applications.
[0065] 2. The total burning time of ten 10 second flame applications (5 samples, 2 applications each) exceeds 50 seconds.
[0066] 3. None of the five samples will flame or emit light to the clamping jaws.
[0067] 4. None of the five samples dripped burning particles that would ignite dry cotton wool located 305 mm below the sample.
[0068] 5. None of the five samples glowed and burned for more than 30 seconds after the flame was removed for the second time.
[0069] The other ratings have a similar format. The most notable difference in the ratings is the time the sample is allowed to support flame combustion or luminous combustion. The flame application time is the same. Here is a brief summary of the required results for V-0, V-1, and V-2: V-0 combustion ceases within 10 seconds after two 10-second flames are applied to the test strip, and no flame dripping is allowed; V-1 combustion ceases within 60 seconds after two 10-second flames are applied to the test strip, and no flame dripping is allowed; and V-2 combustion ceases within 60 seconds after two 10-second flames are applied to the test strip, and flame dripping is allowed.
[0070] The test procedure is outlined here. A sample of specific dimensions is attached vertically to a fixture and flame contact is made for 10 seconds with a 20mm flame. Each of the five samples is clamped 300mm above a layer of dry cotton. A calibrated flame is applied to the bottom edge of the vertically supported test strip for 10 seconds, and any afterflame time (t1) is recorded. When the flame stops, the flame is applied again for an additional 10 seconds, and the afterflame time (t2) and afterglow time (t3) are recorded. If one sample fails, a second set of five samples can be tested. More details can be obtained by contacting UL or by obtaining a copy of this standard and other UL standards by visiting the UL Standards Department website (located at http: / / ulstandardsinfonet.ul.com). Table 1 defines the specific criteria for V-0, V-1, and V-2 ratings.
[0071] Standard conditions V-0 V-1 V2 Afterflame time T1 or T2 for each individual sample, ≦10s ≦30s ≦30s Total afterflame time for any condition group (T1 plus T2 for 5 samples) ≦50s ≦250s ≦250s Afterflame plus afterglow time for each individual flame application (T2+T3) ≦30s ≦60s ≦60s Any residual flame or afterglow of the sample reaching the clamping jaws no no no Cotton indicator ignites from burning particles or drops no no yes
[0072] Implementation
[0073] 1. A composition comprising: a) 30 weight percent or more of one or more post-consumer recycled polycarbonates, b) 5 weight percent or more of one or more virgin polycarbonates, c) one or more silicon compounds having a branched structure and an organic functional group, d) one or more anti-drip agents, e) one or more organic metal salts, f) one or more carbon-based particles, metals or metal oxides, and g) one or more buffers, such as alkali metal phosphates, wherein the weight percentages are based on the total weight of the composition.
[0074] 2. The composition of claim 1 comprising 50 wt% or more of one or more post-consumer recycled polycarbonates.
[0075] 3. The composition of claim 1 comprising 75 wt% or more of one or more post-consumer recycled polycarbonates.
[0076] 4. The composition of claim 1 comprising 90 wt. % or more of one or more post-consumer recycled polycarbonates
[0077] 5. A composition according to any one of the preceding claims, wherein the composition comprises:
[0078] about 0.1 to about 3 weight % of one or more silicon compounds having a branched structure and an organic functional group, d) about 0.01 to about 2 weight % of one or more anti-drip agents, e) about 0.01 to about 2 weight % of one or more organic metal salts, f) about 0.02 to about 10 weight % of one or more carbon-based particles, metals or metal oxides, and g) about 0.02 to about 0.2 weight % of one or more buffer compounds, such as alkali metal phosphates, wherein the weight percentages are based on the total weight of the composition.
[0079] 6. A composition according to any one of the preceding embodiments, wherein the composition comprises:
[0080] c) about 0.1 to about 1.5 weight % of one or more silicon compounds having a branched structure and an organic functional group, d) about 0.01 to about 2 weight % of one or more anti-drip agents, e) about 0.01 to about 1.0 weight % of one or more organic metal salts, f) about 0.03 to about 5 weight % of one or more carbon-based particles, metals or metal oxides, and g) about 0.02 to about 0.1 weight % of one or more buffer compounds, such as alkali metal phosphates, wherein the weight percentages are based on the total weight of the composition.
[0081] 7. The composition according to any of the preceding embodiments, wherein the one or more organometallic salts include one or more perfluoroalkyl sulfur compounds or aromatic sulfur compounds, which are present in an amount of about 0.05 to about 0.4 weight percent based on the composition.
[0082] 8. The composition according to any of the preceding embodiments, wherein the one or more organometallic salts are present in an amount of about 0.05 to about 0.4 weight percent based on the composition.
[0083] 9. The composition according to any one of the preceding embodiments, wherein the composition further comprises one or more non-halogenated flame retardants,
[0084] 10. The composition according to any one of the preceding embodiments, wherein the composition contains one or more antioxidants.
[0085] 11. The composition according to any one of the preceding embodiments, wherein the composition contains one or more UV absorbers.
[0086] 12. The composition according to any one of the preceding embodiments, wherein the composition contains one or more impact modifiers.
[0087] 13. The composition according to any one of the preceding embodiments, wherein the composition contains one or more release agents.
[0088] 14. The composition according to any one of the preceding embodiments, wherein the composition contains one or more colorants.
[0089] 15. A composition according to any of the preceding embodiments, wherein the composition further comprises one or more of the following: one or more non-halogenated flame retardants, one or more antioxidants, one or more UV absorbers, one or more release agents and / or one or more impact modifiers.
[0090] 16. The composition of any one of the preceding embodiments, wherein the one or more colorants are present in an amount from greater than 0 to about 5% by weight of the composition.
[0091] 17. The composition of any one of the preceding embodiments, wherein the one or more non-halogenated flame retardants are present in an amount of about 0.1 to about 20% by weight of the composition.
[0092] 18. The composition of any one of the preceding embodiments, wherein the one or more antioxidants are present in an amount of about 0.0001 to about 1% by weight of the composition.
[0093] 19. The composition of any one of the preceding embodiments, wherein the one or more UV absorbers are present in an amount from greater than 0 to about 0.5% by weight of the composition.
[0094] 20. The composition of any one of the preceding embodiments, wherein the one or more impact modifiers are present in an amount of about 1 to about 2.5% by weight of the composition.
[0095] 21. The composition according to any of the preceding embodiments, wherein the one or more release agents are present in an amount of about 0.1 to about 0.6 wt % of the composition.
[0096] 22. The composition according to any of the preceding embodiments, wherein the one or more organometallic compounds are present in an amount of about 0.05 to about 0.4 weight percent based on the composition.
[0097] 23. The composition according to any of the preceding embodiments, wherein the one or more organometallic compounds comprise one or more alkali metal perfluoroalkyl sulfonates.
[0098] 24. The composition according to any one of the preceding embodiments, wherein the one or more organometallic compounds comprise one or more potassium perfluoroalkyl sulfonates.
[0099] 25. The composition of any one of the preceding embodiments, wherein the one or more carbon-based particles, metals, or metal oxides comprise one or more of carbon black, titanium dioxide, magnesium oxide, silicon dioxide, iron oxide, and aluminum oxide.
[0100] 26. The composition of any one of the preceding embodiments, wherein the one or more metal oxides comprises one or more of titanium dioxide, magnesium oxide, and silicon dioxide.
[0101] 27. A composition according to any of the preceding embodiments, wherein the one or more buffer compounds include one or more alkali metal phosphates, which may include one or more of distearyl pentaerythritol diphosphate, monohydrogen phosphate or dihydrogen phosphate and monohydrogen phosphate, dihydrogen phosphate or trihydrogen phosphate compounds.
[0102] 28. The composition of any one of the preceding embodiments, wherein the one or more alkali metal phosphates comprises one or more monohydrogen phosphate, dihydrogen phosphate, or trihydrogen phosphate compounds.
[0103] 29. The composition according to any one of the preceding embodiments, wherein the one or more alkali metal phosphates comprises sodium dihydrogen phosphate.
[0104] 30. The composition according to any of the preceding embodiments, wherein an article prepared from the composition achieves UL94 V0@1.4 mm flame retardancy and maintains ductility when processed at 300°C for a residence time of 7 minutes or more.
[0105] 31. The composition of any of the preceding embodiments, wherein an article prepared from the composition exhibits a notched Izod impact strength of 700 J / m or greater with a standard deviation of about 25 J / m or less.
[0106] 32. The composition of any of the preceding embodiments, wherein the post-consumer recycled polycarbonate has a melt flow rate of about 1 to about 30 g / 10 min according to ASTM D1238.
[0107] 33. The composition of any of the preceding embodiments, wherein the pristine polycarbonate has a melt flow rate of about 1 to about 30 g / 10 min according to ASTM D1238.
[0108] 34. A molded article prepared from the composition of any one of the preceding embodiments.
[0109] 35. A method comprising: a) intimately contacting and mixing the ingredients of the composition of any one of embodiments 1 to 33 at a temperature of about 250° C. or higher for about 4 minutes or longer, b) filling a mold with the mixed composition of a), and c) forming the composition in the mold into a solid article, and d) removing the formed article from the mold.
[0110] 36. The method according to embodiment 35, wherein the contact mixing is carried out in an extruder and the formed mixture is moved from the extruder to a die.
[0111] 37. The method of embodiment 35 or 36, wherein the contacted components are contacted at a temperature of about 300°C or higher for about 5 minutes or longer.
[0112] Illustrative Embodiments
[0113] The following examples are provided only to illustrate the present invention and are not intended to limit the scope thereof. Unless otherwise indicated, all parts and percentages are by weight.
[0114] Several samples were prepared according to the following procedure. Three components were prepared, namely, PCR raw material, original PC raw material and additive mixture. PCR raw materials of different weight ratios (e.g., 50%, 85% or 95%) were prepared from their different MFR, 6 or 16 g / 10min pellets. The original PC raw material was selected from 3MFR or 23MFR pellet raw materials. The additive mixture mixed all other ingredients with 10MFR original PC powder to form a uniform mixture. Each component was fed into a 40mm twin-screw extruder through a separate K-Tron weight feeder with a barrel temperature of 240-280°C. The composition was melt blended, extruded and crushed into pellets.
[0115] The melt flow rate of the pellets predried at 120°C for 4 hours was measured as described above. The notched Izod value was determined using the following test according to ASTM D256, which is a single-point test that measures the resistance of a material to a pendulum impact. It is defined as the kinetic energy required to initiate fracture and continue fracture until the specimen breaks.
[0116] Tables 2A and B provide experiments showing the flame retardancy of polycarbonate compositions with and without post-consumer recycled polycarbonate PCR.
[0117]
[0118]
[0119] Tables 2A and B show that for experiments E1 to E16 containing 0% to 90% PCR, experiments E1 and E2 belong to the original PC resin without PCR at low MFR and high MFR, respectively. They achieve a V0 rating at 1.4mm thickness. Using 50% PCR resin with the same flame retardant package causes the rating to drop from V0 in E1 and E2 to V1 in E3 and E4 because the burn time exceeds 50 seconds and dripping occurs in E4. Although the E6 sample containing 90% 16MFR PCR PC has a V0 rating, the E5 sample containing 90% 6MFR PCR PC exhibits a V1 rating.
[0120] After adding silicone rubber, the rating dropped from V1 in E3 to V2 in E7 due to dripping, and from V2 in E4 to no rating in E8 due to flame dripping and a burning time of up to 116 seconds. Samples E9-E14 and E16, however, only achieved a V1 rating at a thickness of 1.4 mm using existing flame retardant packaging of silicone compounds containing 50% PCR and 90% PCR. E15 just met the V0 rating standard because only one sample reached 10 seconds. Samples E9-E12 containing 50% PCR had a burning time of more than 50 seconds and were therefore rated V1. Samples E9 and E10 used a combination of charring salts and silicone compounds that just achieved a V1 rating. Samples E13-E16 containing 90% PCR, except E15, all received a V1 rating because individual samples exceeded 10 seconds. Therefore, E9-E16 using existing flame retardant packaging could not meet the V0 standard. In order to improve the flame retardant performance, inorganic substances were added to the existing flame retardant packaging, which shortened the burning time and achieved a V0 rating at a thickness of 1.4mm.
[0121] Table 3 shows experiments E17-E30, which aimed to improve the flame retardancy of polycarbonate containing PCR by adding inorganic substances such as carbon black (C), talc (SiO2 and MgO) and titanium dioxide (TiO2).
[0122]
[0123] The addition of carbon to the 50% PCR carbonized salt samples E3 and E4 reduced the burn time to less than 50 seconds, with no samples exceeding 10 seconds, achieving the V0 rating shown in E17 and E18, respectively. The addition of carbon to the 50% PCR combination samples E9 and E10 and the 90% PCR existing silicone compound samples E13 and E14 reduced the burn time to less than 50 seconds, with no samples exceeding 10 seconds, achieving the V0 rating shown in E19 and E20, and E21 and E22, respectively.
[0124] The addition of TiO2 to the 50% PCR samples in E11 and E12 reduced the burning time to less than 50 seconds, with no samples exceeding 10 seconds, thus achieving the V0 rating shown in E23 and E24. Similarly, the 85% PCR samples treated with the same TiO2 and flame retardant packaging also achieved the V0 rating shown in E25 and E26.
[0125] For E13 and E14 with 90% PCR samples, adding different concentrations of talc, 0.3% and 1.0%, reduced the burning time to less than 50 seconds, with no sample exceeding 10 seconds, thus achieving the V0 rating shown in E27-E28 and E29-E30, respectively. Therefore, inorganic substances can reduce the burning time and help achieve the V0 rating.
[0126] Figure 1 The equation used to calculate the residence time is shown to quantify the thermal stability of the materials of the present invention.
[0127] Residence time (t R ) is the length of time the plastic resides in the molding barrel before being injected. As the plastic moves from the molding machine's feed port to the tool's cavity, the dwell time for the first few shots will be different than the rest of the automated run. Only samples that experience the same dwell time are collected for testing and measurement.
[0128] Cycle time (t c ) is the total time required to complete an injection, covering all stages of the injection cycle. It is the time from mold closing to mold opening in a production cycle, including filling time, packaging time, cooling time, and mold opening time.
[0129] Shot weight (m) is the amount of resin that needs to be injected to fill the mold. It consists of gates, runners, and components that can be weighed. Shot capacity is the maximum weight of material that can be delivered into the injection mold in one injection stroke. It is equal to the cross-sectional area of the barrel. Multiply by the maximum stroke L, that is Then, the dwell time
[0130]
[0131] Where ρ is the melt density of the polymer. For example, molten polyurethane has ρ = 1.08 g / cm 3 (PC solid density = 1.2g / cm 3 ), t c = 26s, D = 4cm, L = 15cm, m = 20.5g, then t R = 4.3 minutes. Therefore, changing the cycle time of the injection molding process can control the residence time.
[0132] Table 4 shows experiments E31 to E34 to show the effect of buffers monosodium phosphate (MSP) and disodium phosphate (DSP) on the thermal stability of polycarbonate resins containing PCR. As shown in E32, the addition of DSP buffer to E4 did not improve its impact strength at a processing temperature of 300°C and a residence time of 5 minutes and above. However, the addition of MSP buffer to E4 slightly increased its impact strength, as shown in E34, indicating a potential benefit of enhanced impact strength.
[0133] Table 4
[0134]
[0135] Tables 5A and B provide data E35 to E50 to illustrate the effect of monosodium phosphate (MSP) on the thermal stability of polycarbonate resins containing PCR. At a low processing temperature of 280°C and a residence time of 4 minutes, the materials of E35 to E50 exhibit similar notched Izod impact strengths of more than 714 J / m, indicating ductile fracture behavior.
[0136]
[0137]
[0138] At higher processing heat conditions, such as 300°C and 5 minutes, 300°C and 6 minutes, and 300°C and 7 minutes, the materials begin to behave differently. At 300°C and 5 minutes, the impact strength of the black compositions E35-E37 containing 50% to 90% PCR begins to decrease and deteriorates with longer residence time (6 and 7 minutes). White compositions E38-E42 exhibit the worst impact strength under these processing conditions, while E39-E40 show that increasing the MBS concentration does not help. The addition of at least 0.02% MSP to the composition increases the ductility of the material, thereby improving its impact strength. This is because these materials exhibit higher average impact strength and narrower deviations. At various PCR content ratios from 50% to 90%, experiments E43-E50 using at least 0.02% MSP showed a greater improvement in impact strength than experiments E35-E42. At 300°C and 6 minutes molding conditions, white compositions E43-E45 and black compositions E46-E50 all exhibited higher average impact strength (≥694 J / m) than E35-E42 (≤547 J / m). Thus, materials containing at least 0.02% MSP perform better than materials without MSP.
[0139] For power adapter applications, the impact strength needs to be further improved because the injection molded plastic housing must withstand a drop impact test. The test is to drop a 0.5kg iron ball from a height of 1.3 meters to five points, four corners and one center on the plastic surface. The test passes if there are no visible cracks or cracks on the surface. To further improve ductility, phenols (AO) are used instead of phosphites. Although the 90% PCR black compositions E47 and E48 containing phosphites AO exhibited ductile impact strengths of 773 and 756 J / m at 300°C and 6 minutes, respectively, the composition E50 containing phenolic antioxidants exhibited a higher impact strength of about 823 J / m, or an increase of about 8%. At 300°C and 7 minutes, the impact strength of sample E50 was 764 J / m, with a deviation of 26 J / m, which is about 30% higher than the average of E47 and E48. Sample E50 passed the drop impact test.
Claims
1. A composition comprising: a) 30 wt. % or more of one or more post-consumer recycled polycarbonates, b) 5% by weight or more of one or more virgin polycarbonates, c) one or more silicon compounds having a branched structure and an organic functional group, d) one or more anti-drip agents, e) one or more organic metal salts, f) one or more carbon-based particles, metal or metalloid oxides, and g) one or more buffer compounds, for example alkali metal phosphates, The weight percentages are based on the total weight of the composition.
2. The composition of claim 1 comprising 90 wt% or more of one or more post-consumer recycled polycarbonates.
3. A composition according to any one of the preceding claims, wherein the composition comprises: c) about 0.1 to about 3 weight percent of one or more silicon compounds having a branched structure and an organic functional group, d) from about 0.01 to about 2 weight percent of one or more anti-drip agents, e) from about 0.01 to about 2 weight percent of one or more organometallic salts, f) from about 0.02 to about 10 weight percent of one or more carbon-based particles, metal or metalloid oxides, and g) from about 0.02 to about 0.2% by weight of one or more buffer compounds, such as alkali metal phosphates, The weight percentages are based on the total weight of the composition.
4. The composition of any one of the preceding claims, wherein the one or more organometallic salts comprises one or more perfluoroalkyl sulfur compounds or aromatic sulfur compounds present in an amount of about 0.05 to about 0.4 weight percent based on the composition.
5. The composition of any one of the preceding claims, wherein the composition further comprises one or more of the following: one or more non-halogenated flame retardants, one or more antioxidants, one or more UV absorbers, one or more mold release agents, one or more colorants and / or one or more impact modifiers.
6. The composition of any one of the preceding claims, wherein the one or more metal oxides comprises one or more of titanium dioxide, magnesium oxide, silicon dioxide, iron oxide, and aluminum oxide.
7. The composition of any one of the preceding claims, wherein the one or more metal oxides comprises one or more of titanium dioxide, magnesium oxide, and silicon dioxide.
8. A composition according to any one of the preceding claims, wherein the one or more alkali metal phosphates include one or more of distearyl pentaerythritol diphosphate, mono- or di-hydrogen phosphates, and mono-, di- or tri-hydrogen phosphate compounds.
9. The composition of any one of the preceding claims, wherein the one or more alkali metal phosphates comprises one or more monohydrogen phosphate, dihydrogen phosphate, or trihydrogen phosphate compounds.
10. The composition of any one of the preceding claims, wherein the one or more alkali metal phosphates comprises sodium dihydrogen phosphate.
11. The composition of any of the preceding claims, wherein an article made from the composition achieves UL94 V0@1.4 mm flame retardancy, maintains ductility when processed at 300°C with a dwell time of 7 minutes or more, and has a notched Izod impact strength of 700 J / m or more with a standard deviation of about 25 J / m or less.
12. A molded article prepared from the composition of any preceding claim.
13. A method comprising: a) contacting and mixing the ingredients of the composition of any one of claims 1 to 11 at a temperature of about 250° C. or higher for about 4 minutes or longer, b) filling the mold with the mixed composition of a), c) forming the composition in the mold into a solid article, and d) removing the formed article from the mold.
14. The method of claim 13, wherein the contact mixing is performed in an extruder and the formed mixture is moved from the extruder to a die.
15. The method of claim 13 or 14, wherein the contacted components are contacted at a temperature of about 300°C or higher for about 5 minutes or longer.
Citation Information
Patent Citations
Flame-retardant, stress crack resistant polycarbonate ABS moulding composition
EP0640655A2
Organopolysiloxane polycarbonate block copolymers
US3419634A
Flame retardant aromatic polycarbonate compositions made from fluorinated diphenols
US4379910A
Interfacial polycarbonate preparation by adding additional solvent
US4529791A
Polycarbonate blends having low gloss
US4677162A